Cognitive Apprenticeship During Preceptorship. Issue 6 (November 2017) - Key, Betty A.; Wright, Vivian H.
Abstract : This study investigated whether implementation of an instructional strategy during hospital orientation preceptorship of newly graduated nurses would impact their confidence and ease of transition. Findings revealed an increase in confidence of newly graduated nurses after implementation of cognitive apprenticeship principles. The findings suggest that it can be beneficial to teaching cognitive apprenticeship principles to preceptors for use during preceptorship.